Fifty shades of kale : 50 fresh and satisfying recipes that are bound to please - Ramsey, Drew (HarperWave, 2013)
"Now for the first time in hardcover, the book has been redesigned; re-shot with beautiful 4-color photography; and re-imagined with new content and recipes. The result is a gorgeous, sexy cookbook that offers readers 50 different ways to enjoy one of the healthiest vegetables in existence. Written with a playful nod to its inspiration, 50 Shades of Kale introduces kale as an enticing seductress whose nutrient powers and mouth-watering flavor make her one sought-after vegetable. The book offers a nutritional overview, kale cooking tips, and a tutorial on the various varieties of kale, as well as 50 delicious ways to have your kale and eat it too"--